2022
DOI: 10.1177/01945998221076482
|View full text |Cite
|
Sign up to set email alerts
|

Resident Burnout and Well‐being in Otolaryngology and Other Surgical Specialties: Strategies for Change

Abstract: Objective To perform a literature review on burnout prevalence, factors that affect burnout and well-being, and solutions to address burnout in otolaryngology–head and neck surgery (OTO-HNS) residents and residents in other surgical specialties. Data Sources Ovid Medline, Embase, and article reference lists. Review Methods A literature search was performed to identify articles on resident burnout, distress, wellness, well-being, and quality of life. Articles deemed outside the scope of the current work were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 92 publications
1
11
0
Order By: Relevance
“…The proportion of depression found in European residents and fellows is higher than in most US studies. 2,3 Notably, the prevalence was higher in residents compared with fellows, which was observed in other studies. 12 It is well known that depressive symptoms may be associated with sleep disturbance, such as insomnia.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…The proportion of depression found in European residents and fellows is higher than in most US studies. 2,3 Notably, the prevalence was higher in residents compared with fellows, which was observed in other studies. 12 It is well known that depressive symptoms may be associated with sleep disturbance, such as insomnia.…”
Section: Discussionsupporting
confidence: 77%
“…Pandemics may be associated with negative outcomes in the workload, stress, sleep and mental health status of health care workers. 2,9,10 Residents and fellows in surgical disciplines, such as otolaryngology-head and neck surgery, are particularly at risk regarding demanding, unpredictable workload, highstakes surgeries, and nights on call. 2,11 In this cohort study, we observed significant rates of depression and sleep disorders in residents and fellows, which have increased throughout the pandemic period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations